Chicken or the Egg: The Reciprocal Association Between Feeding Behavior and Animal Welfare and Their Impact on Productivity in Dairy Cows - Llonch, Pol; Mainau, Eva; Ipharraguerre, Ignacio R.; Bargo, Fernando; Tedó, Gemma; Blanch, Marta; Manteca, Xavier (Frontiers in Veterinary Science, 2018)
Feeding behaviour in dairy cattle has a significant impact on feed efficiency, which is important for increasing the profitability of livestock and, at the same time, reducing the environmental impact. Feeding behaviour can be measured by feeding time, meal duration, meal frequency, feeding rate and rumination time. Higher feed intake is related to lower feed efficiency; whereas an increase in feeding time facilitates chewing, reduces feed particle size and increases its digestibility. More frequent and shorter meals are usually associated with a more efficient use of feed due to improvement of feed digestibility. Rumination time is positively associated with milk production. Impaired health is associated with variations in feeding behaviour, which can be used to identify and predict some diseases such as ketosis, mastitis or lameness. Changes in rumination time are also a reliable indicator of mastitis, lameness, ketosis, abomasal displacement and the onset of calving. In addition to the cause-effect relationship between disease and changes in feeding behaviour, there are also some cases in which changes in feeding behaviour may lead to an increased risk of disease, as exemplified by the relationship of feeding rate with sub-acute ruminal acidosis. Feeding behaviour is regulated by internal and external factors and some of them are relevant for animal welfare. The main welfare-associated factors influencing feeding behaviour are social behaviour and temperament, and environmental effects. Cattle are social animals and hierarchy has a notable impact on feeding behaviour, especially when access to feed is limited. Competition for feed causes a reduction in the average feeding time but increases feeding rate. Excitable animals visit the feeder more often and spend less time per meal. High environmental temperature affects feeding behaviour, as heat-stressed cattle change their feeding pattern by concentrating the feeding events in crepuscular hours, leading to an increased risk of sub-acute ruminal acidosis. In conclusion, feeding behaviour is a determinant feature for improving efficiency, productivity and welfare of dairy cattle. Routine assessment of feeding behaviour allows monitoring of health and production status of dairy cattle at the individual and farm level, which is a useful tool to optimize the management of livestock.